From Direct Provision to Housing: A Qualitative Study of the Housing Journeys of Refugees in Ireland - Bieri, Cordula Doris (Trinity College Dublin. School of Social Work & Social Policy. Discipline of Social Studies, 2024)
This thesis examines the housing journeys of refugees in Ireland, with a particular focus on the transition from Direct Provision to housing. In Ireland and elsewhere, a significant body of literature has examined refugees? experiences of living in reception centres and of accessing housing once they gain status. To date, however, limited attention has been paid to how refugees navigate and make sense of the transition between these two distinct fields of housing, including the strategies they deploy in the search for housing. Initiated in 2018, this research was conducted at a time of significant policy change in relation to refugee reception conditions in Ireland. In 2018, asylum seekers were granted the right to work and, since 2019, two housing Non-Governmental Organisations (NGOs) have been tasked with supporting refugees as they transition from DP to housing. While these changes might be expected to improve refugees? access routes to secure housing, an escalating housing crisis has produced new challenges of access to affordable private rented accommodation. Underpinned by a constructivist epistemology, this research utilised a combination of in-depth interviewing and the ethnographic approach of the `Go-Along?, which involves the researcher and participant walking together and talking in a less formal way about experience, place, perspectives and meanings. Twenty-two refugees from across Ireland, including ten women and twelve men who had gained status within the past ten years were recruited. The use of method triangulation produced a nuanced understanding of the case under study. Mobilising Bourdieu?s Theory of Practice, particularly the concepts of field, capital and practice, enabled an in-depth understanding of refugees? housing journeys. The analysis revealed that while staying in DP, some participants succeeded in improving their accommodation situation by drawing on social links (e.g. to General Practitioners or solicitors). While the superdiverse field of DP at times produced conflicts and tensions, DP also provided a network of close and weak ties, offering participants access to information and practical support. Although gaining refugee status brought feelings of relief associated with having finally escaped a prolonged period of marginalisation, it also led to a sense of fatigue arising from the challenges they had endured during the time spent in DP. In addition, the transition from DP to mainstream welfare provision meant that participants had to learn how to navigate a new bureaucratic field. Low affordability and housing market discrimination, combined with labour market exclusion during the asylum process, meant that they occupied a disadvantaged position in the private rental market. In response to housing exclusion refugees developed housing search strategies involving concealing their economic situation and/or social identity, persuading landlords of their deservingness, adapting or lowering their expectations and searching for accommodation by drawing on co-ethnic networks and social links with NGOs. Detailed analysis of the paths followed by participants in the search for housing revealed that a majority followed linear housing journeys when attempting to secure accommodation in the private rental market with the Housing Assistance Payment. A smaller group followed a turbulent housing journey, having accessed numerous insecure, temporary accommodations through their social networks, and leading some into situations of homelessness. Refugees? perceptions of the private rental market were shaped by their experience of DP: they linked the transition from DP to housing to reclaiming control over their day-to-day lives, finding peace, and regaining a sense of normality. In response to ongoing housing insecurity, refugees adapted their practices by prioritising rental payments, striving to be `good? tenants and delaying entry to the labour market in order to avoid the loss of housing and other welfare supports. Ongoing housing insecurity also undermined their home-making practices and their ability to maintain connections with friends and neighbours. The findings of this research highlight the importance of taking an integrated approach to understanding refugees? housing journeys. The thesis concludes by setting out policy recommendations that highlight the importance of locating refugees? housing needs within mainstream housing policy.
APPROVED
Keywords: Refugees; Direct Provision; Housing Insecurity; Housing Access; Housing Policy; Qualitative Research; Go-Along